Identifikasi Elemen Pembentuk Citra Kota Marisa Menurut Teori Kevin Lynch - Indriani Umar (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
The development of cities in Indonesia is inseparable from identity and characteristics. Kevin Lynch's theory regarding the five elements of the city can be a reference in making the identity or characteristics of a city. This is because each city or region has a characteristic that is different from one city to another. Marisa City is the capital of Pohuwato Regency which also has its own characteristics. Consequently, it is important to identify the five elements of the city according to Kevin Lynch's Theory on Marisa City. This can be the image of Marisa City or the face of Marisa City so that a person or group of people from other regions can recognize Marisa City through the five elements that make up the city according to Kevin Lynch's theory. The purpose of this research is to identify the image-forming elements of Marisa City according to Kevin Lynch's Theory. The method used in this study is a qualitative descriptive method with data collection techniques through field observations and interviews. The results of this study are that in terms of Kevin Lynch's theory regarding city-forming elements, Marisa City has five elements that form the city's image, namely 1) Landmark elements marked by the Panua Monument and the Tree of Love Beach Plaza; 2) Elements of Paths, namely on the path on Jl. Harbour, Jl. Trans Sulawesi, Jl. Diponegoro, and Jl. Gen. Sudirman; 3) Nodes elements, namely at the intersection of Jl. Gen. Sudirman and Jl. Trans Sulawesi, intersection Jl. Sudirman and Jl. Diponegoro, and the intersection of Jl. Sudirman and Jl. Harbor; 4) District elements, namely the Pohuwato Regency government office block plan area; and 5) Edge elements, namely Marisa River and Tomini Bay.